English Clause Complex Analysis on Thai Lottery Rituals from the Perspective of SFL: Integration of Western Language Theory into Eastern World - Preecha, Parinyaporn; Srinon, Udomkrit (วารสารมนุษยศาสตร์ มหาวิทยาลัยมหามกุฏราชวิทยาลัย; Vol 10 No 1 (2018): วารสารมนุษยศาสตร์ มหาวิทยาลัยมหามกุฏราชวิทยาลัย, 2021)
Western bloggers from Thaisabai.org found that the Thai people are crazy about lottery rituals which may seem strange to outsiders. According to their critics on Thai lottery rituals, the farangs (Westerners) may approach the subjects of Thai studies, but are unable to gain insight and intimacy. Therefore, this study attempts to apply SFL (Systemic Functional Linguistics) for better understanding on Thai identity in a Thai context. To study SFL linguistic resources from this data, this paper discusses the meanings of clauses by a series of process that are combined in the logical process of the clauses. Theoretically, complex clauses can be combined through one of two logical semantic relationships: expansion or projection. Therefore, this study aims to analyse the English text on Thai lottery rituals from Thaisabai.org. Based on the perspective of Systemic Functional Linguistics (Halliday 1985a, 1985b, 1994), the analysis revealed that there are two types of logical semantic relations: expansion and projection are embedded and realized in the text through a system of mutual dependence or taxis that can be divided into paratactic and hypotactic relations.